Effects of mesoscale gravity waves on sporadic E simulated by a one-dimensional dynamic model - Xu Zhou; ZeZhong Li; XinAn Yue; LiBo Liu (Earth and Planetary Physics)
In addition to being driven by tidal winds, the sporadic E (Es) layers are modulated by gravity waves (GWs), although the effects are not yet comprehensively understood. In this article, we discuss the effects of mesoscale GWs on the Es layers determined by using a newly developed model, MISE-1D (one-dimensional Model of Ionospheric Sporadic E), with low numerical dissipation and high resolution. Driven by the wind fields resolved by the high-resolution version of the Whole Atmosphere Community Climate Model with thermosphere and ionosphere extension (WACCM-X), the MISE-1D simulation revealed that GWs significantly influence the evolution of the Es layer above 100 km but have a very limited effect at lower altitudes. The effects of GWs are diverse and complex, generally including the generation of fluctuating wavelike structures on the Es layer with frequencies similar to those of the GWs. The mesoscale GWs can also cause increases in the density of Es layers, or they can disperse or diffuse the Es layers and increase their thickness. In addition, the presence of GWs is a key factor in sustaining the Es layers in some cases.